Paradigma Pembelajaran Iqra Dalam Membangun Karakter Bangsa - Abdussalam, Aam; Hidayat, Tatang; Istianah, Istianah (Civilization Research: Journal of Islamic Studies, 2022)
The purpose of this study is to determine the iqra learning paradigm in building the nation's character. This research uses a qualitative approach and a literature study method. Based on the results of the study, the iqra paradigm in learning is able to touch the substantive meaning, namely the ruhiah aspect, where education almost loses this aspect. There are at least two aspects that must exist in the world of education today, namely the aspect of affection and directionality of values. The approach of compassion and the development of divine values should be integral in the entire educational effort. Because the success of education cannot be separated from these two aspects. How these aspects are read and absorbed by students in educational communication delivered by the teacher.